Biomechanical Properties of Bioabsorbable Fixation for Osteochondral Shell Allografts - Thomas, Dimitri M.; Stannard, James P.; Pfeiffer, Ferris M.; Cook, James L. (The Journal of Knee Surgery, 2020)
This study compares bioabsorbable nail to metal screw fixation of shell osteochondral allograft (OCAs) for compression and shear strength. Cadaveric distal femurs (n = 5) yielding six 1.5 cm shell grafts (n = 30) were used. Three different fixation methods (2.0 and 2.4 mm headed screws, and copolymer absorbable nail) were compared for statistically significant differences (p < 0.05) in contact area, contact pressure, and shear load-to-failure. No significant differences in contact areas existed among groups (224 ± 33.5 mm2; 233.9 ± 20.8 mm2, 220.6 ± 22.7 mm2; p = 0.509 for 2.4, 2.0 mm screw, and nail, respectively). No significant differences in contact pressures existed (1.7 ± 0.6 MPa/mm2, 1.5 ± 0.8 MPa/mm2, 1.4 ± 0.9 MPa/mm2; p = 0.73 for 2.4, 2.0 mm screw, and nail, respectively). Load-to-failure for each was: 280.7 ± 48.4 N for 2.4 mm screws, 245.1 ± 70.6 N for 2.0 mm screws, and 215.2 ± 39.4 N for nails. There were no statistically significant differences in load-to-failure between 2.4 and 2.0 mm screws (p = 0.29) or between 2.0 mm screws and nails (p = 0.23); however, load-to-failure in shear was significantly higher for 2.4 mm screws compared with nails (p = 0.036). Fixation of shell OCAs using a copolymer headed nail provides initial graft-recipient compression similar to fixation using 2.0 and 2.4 mm headed screws. Nails failed in shear at significantly lower load than 2.4 mm screws but not 2.0 mm screws which have proven adequate for clinical healing. This study has clinical relevance, as a copolymer bioabsorbable headed nail (SmartNail) has graft-recipient compression and shear load-to-failure properties that suggest it is viable for shell OCA fixation.
Keywords: osteochondral allograft; shell allograft; osteochondral allograft fixation; PLLA implant; bioabsorbable pin